22.6k views
25 votes
Evaluate each of the expressions in the list for y = 5. Drag and drop the correct number into each box to

complete each equation. Then match the equivalent expressions.
View Example
Step-by-step
List A
List B
36
Textbook
6+by =
by-63
24
Print
6ły - 1) =
bly + 1) =
31
by+1=
1+ y =
The expression 6 + 6y is equivalent to the expression select)
The expression bly - 1) is equivalent to the expression select)
The expression by + 1 is equivalent to the expression select) v
Tumit

Evaluate each of the expressions in the list for y = 5. Drag and drop the correct-example-1

1 Answer

5 votes

Answer:

Explanation:

To get the value of the expressions in list A and list B we will substitute y = 5 in each expression.

List A List B

1). 6 + 6y = 6 + 6(5) = 36 6y - 6 = 6(5) - 6 = 24

2). 6(y - 1) = 6(5 - 1) = 24 6(y + 1) = 6(5 + 1) = 36

3). 6y + 1 = 6(5) + 1 = 31 1 + 6y = 1 + 6(5) = 31

Therefore, (6 + 6y) is equivalent to 6(y + 1)

6(y - 1) is equivalent to (6y - 6)

(6y + 1) is equivalent to (1 + 6y)

User RocketNuts
by
5.7k points